(untitled) (Journal of Imam Al-Kadhim College, 2023)
Abstract: Man bases his understanding of the surroundings on similar images which he compares in his mind with the reality he experiences in his marching to facts. Human nature believes that there is an example or a model seen and then its action, saying and verification is copied and the Holy Qur’an refers to this fact by saying “And you had a good example in the Messenger of Allah.” Accordingly, it is necessary to try to pick out a model related to representation (representative methodology) that has rules, criteria and types as other scholarly methodologies such as the descriptive, historical and contrastive because the structure of human thought always tends to use representation to reach the facts of things.